Archean to early Paleoproterozoic iron formations document a transition in iron oxidation mechanisms. (15th February 2023) - Wang, Changle; Robbins, Leslie J.; Planavsky, Noah J.; Beukes, Nicolas J.; Patry, Laureline A.; Lalonde, Stefan V.; Lechte, Maxwell A.; Asael, Dan; Reinhard, Christopher T.; Zhang, Lianchang; Konhauser, Kurt O.
Abstract: It is generally accepted that photosynthetic marine planktonic bacteria were responsible for the oxidation of dissolved ferrous iron (Fe(II)) and the subsequent deposition of iron formations (IFs) throughout the Archean and early Paleoproterozoic. However, the relative roles of the different biological Fe oxidation mechanisms in driving IF deposition—such as anoxygenic photosynthesis (photoferrotrophs) and oxygenic photosynthesis (cyanobacteria)—remain poorly resolved. Here, we present coupled bulk-rock Fe isotope and manganese (Mn) versus Fe ratios from Archean to early Paleoproterozoic IFs in order to provide a new perspective on Earth's early redox history and processes leading to IF deposition. Based on this updated IF geochemical record, we bolster the case that the partial oxidation of Fe(II) to Fe(III) was central to IF genesis, arguing against extensive water column Fe(II) silicate formation as the main process driving IF deposition. The geochemistry of IFs deposited prior to the Great Oxidation Event (GOE) shows that partial Fe(II) oxidation was a common feature in either anoxic or low oxygen (O2 ) conditions, where metabolic Fe(II) oxidation by photoferrotrophs is likely to have prevailed over ambient Fe(II) oxidation by O2 produced by cyanobacteria. Assuming that cyanobacteria evolved in the Archean, the presence of partial Fe(II) oxidation suggests that O2 production was relatively muted during this time. This points to a model for Archean surface redox conditions, whereby oxygen oases were relatively limited in extent, likely due to low primary productivity of cyanobacteria and high Fe fluxes. We further demonstrate a gradual displacement of metabolic Fe(II) oxidation in the Archean by quantitative O2 -driven Fe(II) oxidation during the GOE by ca. 2.31 Ga.